Did the euro change the nature of FDI flows among member states? - David Sondermann; Isabel Vansteenkiste (European Central Bank (ECB), 2019)
In this paper we investigate the impact of the euro integration process on the drivers of FDI inflows. We show theoretically and empirically that the single currency alters the drivers of FDI inflows across its Member States. Estimating bilateral gravity models of FDI inflows into euro area countries, we show that the euro facilitates intra-euro area vertical FDI flows but reduces incentives for horizontal or market seeking FDI. Instead, horizontal FDI flows stemming from investor countries located outside the monetary union increase. Such flows are however not more likely be directed towards euro area countries with larger domestic markets but rather to countries that are close to large euro area markets and that have higher quality institutions. Overall, these results suggest that while the euro has been beneficial to FDI inflows into the monetary union, the impact differs significantly across countries. The global financial crisis does not change our main findings. Our results are robust to various economic specifications.
Keywords: F21; F23; F45; O43; 330; Foreign direct investment; euro; economic structures; institutions; euro area countries